Pre-Stroke Modified Rankin Scale: Evaluation of Validity, Prognostic Accuracy, and Association with Treatment - Terence J. Quinn; Martin Taylor‐Rowan; Aishah Coyte; Allan Clark; Stanley D. Musgrave; Anthony K. Metcalf; Diana J. Day; Max Bachmann; Elizabeth A. Warburton; John F. Potter; Phyo Kyaw Myint (2017)
The modified Rankin Scale (mRS) was designed to measure poststroke recovery but is often used to describe pre-stroke disability. We sought to evaluate three aspects of pre-stroke mRS: validity as a measure of pre-stroke disability; prognostic accuracy and association of pre-stroke mRS scores, and process of care.We used data from a large, UK clinical registry. For analysis of validity, we compared pre-stroke mRS against other markers of pre-stroke function (age, comorbidity index, care needs). For analysis of prognostic accuracy, we described univariable and multivariable models comparing pre-stroke mRS and other prognostic variables against a variety of outcomes (early and late mortality, length of stay, institutionalization, incident complications). Finally, we described association of pre-stroke mRS and components of evidence-based stroke care (early neuroimaging, admission to stroke unit, assessment of swallow).We analyzed data of 2,491 stroke patients. Concurrent validity analyses suggested statistically significant, but modest correlations between pre-stroke mRS and chosen variables (rho >0.40; p < 0.0001 for all). Every point increase of pre-stroke mRS was associated with poorer outcomes for our prognostic variables (unadjusted p < 0.001). This association held when corrected for other covariates. For example, pre-stroke mRS 4-5 odds ratio (OR): 6.84 (95% CI: 4.24-11.03) for 1 year mortality compared to mRS 0 in adjusted model. There was a difference between pre-stroke mRS and treatment, with higher pre-stroke mRS more likely to receive evidence-based care.Results suggest that pre-stroke mRS has some concurrent validity and is a robust predictor of prognosis. This association is not explained by the influence of pre-stroke mRS on care pathways.